2011
DOI: 10.1086/662680
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Elevated Temperature and Pco2Reduces Respiration Rate and Energy Status in the PeriwinkleLittorina littorea

Abstract: In the future, marine organisms will face the challenge of coping with multiple environmental changes associated with increased levels of atmospheric Pco(2), such as ocean warming and acidification. To predict how organisms may or may not meet these challenges, an in-depth understanding of the physiological and biochemical mechanisms underpinning organismal responses to climate change is needed. Here, we investigate the effects of elevated Pco(2) and temperature on the whole-organism and cellular physiology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 82 publications
2
63
1
1
Order By: Relevance
“…High CO 2 decreases the metabolic rate in the mussel Mytilus galloprovincialis , the snail Littorina littorea (Melatunan et al, 2011), the thecosome pteropod Limacina helicina antarctica (Seibel et al, 2012) and the Humbolt squid Dosidicus gigas (Rosa and Seibel, 2008). Other research found an increase in metabolic rate of the pteropod Limacina helicina (Comeau et al, 2009(Comeau et al, , 2010a and in the bivalve Laternula elliptica (Cummings et al, 2011), whereas there was no change in the metabolic rate of the cuttlefish Sepia officianlis (Gutowska et al, 2008) and the mussel Mytilus edulis (Thomsen and Melzner, 2010).…”
Section: Speciesmentioning
confidence: 95%
“…High CO 2 decreases the metabolic rate in the mussel Mytilus galloprovincialis , the snail Littorina littorea (Melatunan et al, 2011), the thecosome pteropod Limacina helicina antarctica (Seibel et al, 2012) and the Humbolt squid Dosidicus gigas (Rosa and Seibel, 2008). Other research found an increase in metabolic rate of the pteropod Limacina helicina (Comeau et al, 2009(Comeau et al, , 2010a and in the bivalve Laternula elliptica (Cummings et al, 2011), whereas there was no change in the metabolic rate of the cuttlefish Sepia officianlis (Gutowska et al, 2008) and the mussel Mytilus edulis (Thomsen and Melzner, 2010).…”
Section: Speciesmentioning
confidence: 95%
“…However, the ability to cope with chronic exposure to elevated pCO 2 conditions appears to be characterized by the acquisition of moderately lower metabolic rates (on average 223% in this study) in both the acclimatized and the adapted species. While metabolic depression in the short term helps an organism to maintain a balance between energy supply and demand [15,16,25,26,111], in the longer term it can rstb.royalsocietypublishing.org Phil Trans R Soc B 368: 20120444 involve the reorganization of its energy budget, often leading to a decrease in its scope for growth and reproduction [2].…”
Section: (A) Discriminating Between Acclimatization and Adaptationmentioning
confidence: 99%
“…For example, in Antarctic fish, it has been found that above their optimal temperature range, cellular processes switch from mainly carbohydrate (glucose and glycogen) to lipid and finally protein metabolism [6]. Other studies on marine gastropods into the effects of sub-lethal elevations in temperature reveal the accumulation of 'end-product' metabolites (lactate and succinate) while ATP concentrations remain stable, indicating an increased reliance on anaerobic metabolism with temperature, using carbohydrates as the energy source [7]. Plasticity of such metabolic processes may be vital in widespread, more northerly distributed species, as organisms encounter increasingly variable climates with latitude [8].…”
Section: Introductionmentioning
confidence: 99%